The person-centered therapy as intervention tools in group counseling for counselors - Fadli, Rima Pratiwi; Suhaili, Neviyarni; Karneli, Yeni; Netrawati, Netrawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Guidance and counseling services in schools still do not provide enough counseling and group therapy. One of the reasons why the service isn't up to par is because the counseling teacher lacks certain talents, particularly when it comes to counseling approaches. As a result, a separate investigation on the counseling strategy is required. As a result, the author delivers a concept paper on one counseling and group treatment strategy. After reviewing a variety of scientific sources, this manuscript was created. This article examines Carl Rogers' client-centered approach, often known as self-counseling, as a counseling intervention tool. It is intended that this script will assist school counselor in giving references for counseling and group therapy implementation in schools.